University students' knowledge and perceived adequate conduct in cases of acute stroke (Bioscience Journal, 2018)
The ability of the general population to recognize the initial symptoms of acute stroke is important for the prevention of neurological damage. The objective of this study was to investigate the knowledge held by university students in health fields and what they perceived was adequate conduct after recognizing that someone is having an acute stroke. The students took a semi-structured, two-part questionnaire, with the first part referring to social and demographic data and the second containing a description of stroke's typical clinical presentation and open-ended questions about it. Of the participants, 86.24% were able to recognize stroke. When comparing the initial and final years, the students in their final years had approximately a 10% increase in stroke recognition. Regarding the perceived correct conduct, it was observed that 84.60% of the students in the initial years would have the right conduct compared to 89.32% of the students in the final years. Even though a high percentage of students demonstrated some knowledge about stroke it is important that we aspire to further educate them about the subject, enabling them to eventually contribute to the general population's education and to promote health.